Oocyte donation following ischemic ovarian detorsion for twisted pedicle due to paratubal cyst - Rojas-Ruiz, Juan C. (2023)
Adnexal torsion is secondary to generally benign ovarian cysts. The usual surgery issalpingo-oophorectomy. However, to maintain ovarian function, minimally invasivesurgery with detorsion and preservation of the ovary is recommended regardless ofits appearance. We present the case of a 19-year-old woman diagnosed with twistedpedicle cyst, who underwent laparoscopic detorsion of the twisted pedicle and excisionof the paratubal cyst with ovarian preservation, despite its ischemic aspect. Thepatient presented favorable evolution and participated in an ovodonation program,obtaining oocytes from the previously affected ovary in similar quantity and quality tothe unaffected ovary. Laparoscopic ovarian detorsion and preservation of the involvedovary regardless of its appearance is a safe and effective procedure to preserve fertility.